Protiv atomnoi ugrozy . Protiv atomnoi ugrozy . Against Atomic Threat . Против атомной угрозы - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Reportage on the nongovernmental conference "Nuclear Tests: From Moratorium to Universal Prohibition" held in the Novaya Zemlya archipelago; discussion of nuclear testing. Featured in the program: Vorontsov, Nikolai Nieolaevich (People's Deputy of the Russian Federation); Vishniakov, Aleksandr Al'bertovich (Member of the Supreme Council of the Russian Federation) Contributors: Torchinskii, Sergei (Anchor) Репортаж о неправительственной конференции "Ядерные испытания: от моратория к всеобщему запрету" на архипелаге Новая Земля; дискуссия о ядерных испытаниях. В программе участвуют: Воронцов, Николай Ниеолаевич (Народный депутат Российской Федерации); Вишняков, Александр Альбертович (Член Верховного совета Российской Федерации) Создатели: Торчинский, Сергей (Ведущий/Ведущая)